2020
DOI: 10.3389/fbioe.2020.00887
|View full text |Cite
|
Sign up to set email alerts
|

Overview on Multienzymatic Cascades for the Production of Non-canonical α-Amino Acids

Abstract: The 22 genetically encoded amino acids (AAs) present in proteins (the 20 standard AAs together with selenocysteine and pyrrolysine), are commonly referred as proteinogenic AAs in the literature due to their appearance in ribosome-synthetized polypeptides. Beyond the borders of this key set of compounds, the rest of AAs are generally named imprecisely as non-proteinogenic AAs, even when they can also appear in polypeptide chains as a result of post-transductional machinery. Besides their importance as metabolit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 281 publications
(512 reference statements)
0
3
0
Order By: Relevance
“…An example is hydroxyproline, which is produced from proline by peptidyl proline hydroxylase after protein synthesis. Amino acids can be classified as nutritionally essential (indispensable) or non-essential (dispensable) [ 73 ].…”
Section: Physiological Importance Of Amino Acidsmentioning
confidence: 99%
“…An example is hydroxyproline, which is produced from proline by peptidyl proline hydroxylase after protein synthesis. Amino acids can be classified as nutritionally essential (indispensable) or non-essential (dispensable) [ 73 ].…”
Section: Physiological Importance Of Amino Acidsmentioning
confidence: 99%
“…In-depth research on multi-enzyme reactions revealed that most reactions maximize the performance of multi-enzyme complexes by placing the enzymes as close together as possible. Therefore, nucleic acids and proteins have been used as scaffolds to shorten the distance between enzymes and accelerate the reaction [17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Noncanonical amino acids, which are not naturally encoded into proteins, have unusual biological activities in their optically pure form and are important building blocks of agrochemicals and pharmaceuticals. For example, l -phosphinothricin is a promising herbicide; l - tert -leucine, l -homoalanine, and l -phenylglycine are used to synthesize the anti-AIDS drug atazanavir, the anti-epileptic levetiracetam, and the antibiotic clopidogrel, respectively; l -norvaline and l -homophenylalanine are the building blocks for angiotensin converting enzyme (ACE) inhibitors, such as perindopril, benazepril, captopril, enalapril, lisinopril, and quinapril. Biocatalytic synthesis of these chiral amino acids with high optical purity is a reliable, scalable, and preferred route owing to its remarkable chemo-, regio-, and stereoselectivity features, coupled with safety and environmental benefits. , Among them, the asymmetric reductive amination of prochiral keto acids catalyzed by amino acid dehydrogenase (AADH) is a very efficient strategy for the production of noncanonical chiral amino acids, with advantages like direct use of cheap ammonia as the amino donor, high atom utilization, and high optical purity of the products (often exceeding 99%). However, though numerous AADHs have been identified and classified according to their substrate specificities, such as glutamate dehydrogenase (GluDH), leucine dehydrogenase (LeuDH), and phenylalanine dehydrogenase (PheDH), only a few AADHs have considerable potential as biocatalysts for the reductive amination processes .…”
Section: Introductionmentioning
confidence: 99%